Arbuscular mycorrhizal fungi and rhizobium facilitate nitrogen uptake and transfer in soybean/maize intercropping system - Meng, Lingbo; Zhang, Aiyuan; Wang, Fei; Han, Xiaoguang; Wang, Dejiang; Li, Shumin (Frontiers in Plant Science, 2015)
The tripartite symbiosis between legumes, rhizobia and mycorrhizal fungi are generally considered to be beneficial for the nitrogen (N) uptake of legumes, but the facilitation of symbiosis in legume/non-legume intercropping systems is not clear. Therefore, the aims of the research are as follows: 1) to verify if the dual inoculation can facilitate the N uptake and N transfer in maize/soybean intercropping systems and 2) to calculate how much N will be transferred from soybean to maize. A pot experiment with different root separations (solid barrier, mesh (30 µm) barrier and no barrier) was conducted, and the 15N isotopic tracing method was used to calculate how much N transferred from soybean to maize inoculated with arbuscular mycorrhizal fungi (AMF) and rhizobium in a soybean (Glycine max L.cv. Dongnong No.42)/maize (Zea mays L.cv. Dongnong No.48) intercropping system. Compared with the Glomus mosseae inoculation (G.m.), Rhizobium SH212 inoculation (SH212), no inoculation (NI), the dual inoculation (SH212+G.m.) increased the N uptake of soybean by 28.69%, 39.58% and 93.07% in a solid barrier system. N uptake of maize inoculated with both Glomus mosseae and rhizobium was 1.20, 1.28 and 1.68 times more than that of G.m., SH212 and NI, respectively, in solid barrier treatments. In addition, the amount of N transferred from soybean to maize in a dual inoculation system with a mesh barrier was 7.25 mg, 7.01 mg and 11.45 mg more than that of G.m., SH212 and NI and similarly, 6.40 mg, 7.58 mg and 12.46 mg increased in no barrier treatments. Inoculating with both AMF and rhizobium in the soybean/maize intercropping system improved the N fixation efficiency of soybean and promoted N transfer from soybean to maize, resulting in the improvement of yield advantages of legume/non-legume intercropping.